Trajetórias de escolarização: um estudo sobre egressos do curso técnico em economia doméstica - Manzan, William Alexandre [UNESP] (2014)
This paper presents the results of a research that examined gender issues in schooling trajectories of four graduates (two men and two women) Technical course in Home Economics, derived from the same public education establishment. The object of study analyzed consisted of the primary provisions of the relationships within gender, assimilated within their families and progenitor consolidating and restructuring the same formulation as the habitus of graduates in their school routes; in matrimonial strategies; in professional careers; cultural and social capital; and strategies for sex education and sexuality. Data collection took place between the period 2011 to 2012, was conducted through questionnaires and interviews with the selected graduates. The analysis used data from categories of method and analysis of Pierre Bourdieu to classification and assessment of the primary provisions that have manifested in a distributed manner in different contexts of the trajectories of the agents. Gendered provisions which necessarily became part and interact with the habitus of agents. After analyzing the categorization of accounts of life histories, it was observed that the habitus of gender restructured the trajectories of schooling continued directing and permeating the professional agents of social background and matrimonial strategies; it was noted also that the gendered habitus was shared by the social status of families constituted by agents and will now play in the offspring the same pattern of sex education strategy narrated in the period of childhood and youth of the same, ie, they stood historical regularities paternal silence and the division of the tract of sexuality as an educational action of the children between the mother figure and school agencies